2023
DOI: 10.19160/e-ijer.1208464
|View full text |Cite
|
Sign up to set email alerts
|

Öğretmen Adaylarının Eleştirel Dinlemeye Yönelik Tutumları

Abstract: Konuşmada aktarılanları incelemek, derinliğine inmek, karşılaştırmak, doğruluğunu, geçerliliğini ve tutarlılığını değerlendirmek şeklinde tanımlanan eleştirel dinleme, algılamanın ve eleştirel düşünmenin bir birleşimi olarak kabul edilir. Bu araştırmanın amacı, öğretmen adaylarının eleştirel dinlemeye yönelik tutumlarını çeşitli değişkenler açısından incelemektir. Nicel araştırma yöntemlerinden betimsel tarama modelinde gerçekleştirilen araştırmanın çalışma grubunu Bartın Üniversitesi Eğitim Fakültesinde İlköğ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…On the other hand, there are also studies that have found that female pre-service teachers have more positive attitudes towards technology than male preservice teachers, and their attitude levels are higher (Yaman, 2007;Özarslan, et al, 2013;Metin et al, 2013;Dargut & Çelik, 2014;Gülen, 2021). There are also studies that show no significant difference in the attitudes of teachers and pre-service teachers towards technology according to gender (Deniz et al, 2006;Şimşek, 2015;Karasakaloğlu et al, 2011;Sipahioğlu, 2019;Arslan & Bilgin, 2020;Ardıç, 2021).…”
Section: Discussion Conclusion and Recommendati̇onsmentioning
confidence: 99%
“…On the other hand, there are also studies that have found that female pre-service teachers have more positive attitudes towards technology than male preservice teachers, and their attitude levels are higher (Yaman, 2007;Özarslan, et al, 2013;Metin et al, 2013;Dargut & Çelik, 2014;Gülen, 2021). There are also studies that show no significant difference in the attitudes of teachers and pre-service teachers towards technology according to gender (Deniz et al, 2006;Şimşek, 2015;Karasakaloğlu et al, 2011;Sipahioğlu, 2019;Arslan & Bilgin, 2020;Ardıç, 2021).…”
Section: Discussion Conclusion and Recommendati̇onsmentioning
confidence: 99%